Screening for language development of preterm infants: relationship between two assessment instruments - Beatriz Servilha Brocchi; Maria Cecília Marconi Pinheiro Lima (Revista CEFAC, 2021)
ABSTRACT Purpose: to associate two screening instruments used to assess global and language development of preterm infants. Methods: a study including 69 children aged 0-24 months of corrected age, premature at birth, who were admitted to the Neonatal Intensive Care Unit (NICU). Researchers used an anamnesis and two protocols: Early Language Milestone Scale (ELM) and Observation and Monitoring Guide for Children from 0-48 months of age. According to the categorical and numerical variables, the protocols were associated with each other through descriptive percentages and non-parametric statistical tests, such as the Chi-square, Spearman's rank correlation coefficient and Mann-Whitney U, Kruskal-Wallis test and multiple correspondences (p<0.05). Results: a significant relationship was found between the Guide and the ELM, since the “not expected for the age” classification was associated with delayed/pathological classification in the Guide, while “expected” results were related to “adequate”. There was also a relationship between the percentile of both instruments, as the higher the Guide value, the higher the ELM values (ELM-R=0.564; p=0.000), suggesting that both protocols complement each other in the evaluation results. Conclusion: the protocols for the assessment of language acquisition in children showed to be complementary, providing a complete assessment and relevant data on the development of preterm infants.